Development of Enzyme-Based Biosensor for the Detection of Formaldehyde in Fish - Marzuki, Nur Indang (2011)
Usage of formaldehyde as preservative in fish by fisherman in order to maintain its fresh look and avoid microbial spoilage is a big risk to consumer’s health. Moreover, its capability to induce carcinogen at certain level arises endeavour to create simple, sensitive and rapid device for formaldehyde determination. Therefore, a novel detection method based on amperometric biosensor coupled with an enzyme, formaldehyde dehydrogenase (FDH) has been developed. To maximize the reaction rate, the enzyme acts as biorecognition was immobilized in Nafion membrane which chemically modified on gold electrode. The enzyme required nicotinamide adenide dinucleotide (NAD+) as a cofactor which then reduced to NADH at -0.2 volt during enzymatic reaction. Through the electrode this physiochemical changes were converted into electric signal which correlated with formaldehyde concentration. The current measurement was analysed using a computer connected to the transducer. The optimized formaldehyde biosensor displayed a linear response over the range of 1 to 10 ppm formaldehyde with correlation coefficient (R2) equals to 0.9865 (RSD <3.05%). The limit of detection (LOD) calculated was 0.016 ppm of formaldehyde and the sensitivity was 7.0264 nA ppm-1. The response time of formaldehyde biosensor was found less than 1 min and has an optimum pH of 8. Besides, it also showed reproducibility with no significant different (p > 0.05) at 1, 5 and 10 ppm of formaldehyde (n = 10). For selectivity and interferences by ratio study, it was discovered that the biosensor response retained its specificity for formaldehyde and did not respond to equivalent additions of methanol and also ethanol and gave the percentage of formaldehyde recovered ranging from 99.0% to 99.8%. The developed biosensor has been applied for monitoring formaldehyde level in Indian Mackerel (Rastrelliger kanagurta) where the samples stored for ten days at temperature of 4oC ± 1 and were compared to formaldehyde levels determined by the conventional Nash method. As the result, the two methods showed a linear correlation coefficient with R2 = 0.9937 (y = 0.0542x - 0.0256) and has no significant different (p > 0.05). For determination of formaldehyde in fish tissue, the percentage of formaldehyde recovery was found at the range of 68.3 to 86.25 (RSD ≤ 10.81%) after spiked with 1, 5 and 10 ppm of formaldehyde. It also showed stable measurement reading of 90% from the initial value after six months (stored at 4oC). Another advantage of the constructed biosensor in this work is the assembly of the basic requirements for simplicity, reusability and reagentless system. Thus, it is a promising tool and has a potential application for fast and direct formaldehyde detection in fish.